Problems and Challenges Associated with Value Addition: With Special Reference to Coconut Based Productions in Jaffna District - Sathana, V. (University of Kelaniya, 2017)
Coconut is one of the major source of Jaffna District. It has the greatest prospects for growth and development. The coconut based producers have been facing huge problems. Value addition in each aspect of coconut based productions create more quality and adequate demand for the products. The purpose of this research is to diagnose the tremendous problems and challenges for value addition of coconut based productions in Jaffna District. Initially this paper reviewed the existing literature, empirical studies as well as the prevailing data bases in order to identify the problems and challenges for value addition. Then researcher conducted qualitative exploratory narrative research on coconut based productions in Jaffna District. Subjects were the owners or managers of enterprises and purposive sampling technique was utilized to select the subjects for this research. Unstructured interview was conducted to collect data. The problems and challenges of entrepreneurs regarding value addition were categorized with coding method by using NVIVO software. Present study identified two types of problems; internal and external problems associated with value addition. This research had two coin side implication, for owners of enterprises and other stakeholder to improve the productivity of organizations.
Keywords: Value Addition; Problems and Challenges; Coconut based Production